Capital Structure Choice in SMEs: Evidence from Kazakhstan - Samal Kokeyeva; Ainagul Adambekova (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
Background - The article examines the factors influencing the decision on the company's capital structure. Along with the standard factors of the company, we also analyze the impact of the industry affiliation of the company on its capital structure. Purpose - to test standard firm factors and industry affiliation of firms affecting the capital structure of SMEs. Design/Methodology/Approach – the non-financial firms in Kazakhstan with all types of economic activities for 2015-2018 under consideration. In order to study the determinants of capital structure such as asset tangibility, size, growth, liquidity, profitability across the industry group of SMEs for non-financial SMEs in Kazakhstan the authors use panel data analysis. Findings - The results indicate that the main factors influencing the process of capital structure management in Kazakhstan SMEs are asset tangibility, size and profitability.  It was confirmed that sectoral implications also affect the long-term debt and total debt of SMEs. Research limitation - it is necessary to provide further research concerning this topic. It is needed to study the capital structure of SMEs in the long term and across multiple countries, which will give us a more accurate concept of decisions on the capital structure taken in companies. Originality/value - the study of capital structure determinants of SMEs in Kazakhstan was not conducted yet. The empirical analysis in many aspects gives the same results as other related studies in emerging markets.  However, the size has a negative relation to the capital structure, which does not correspond to most empirical studies.